Changes in Attitudes Towards Science-Technology-Society of Pre-service Science Teachers - Kaya, Osman Nafiz; Yager, Robert; Dogan, Alev (Springer, 2009)
This research focuses on use of a triadic teaching approach in a science-technology-society (STS) course designed for future science teachers for middle schools in Turkey. Forty-three pre-service science teachers were enrolled in a semester-long course organized around issues students identified and used throughout the semester. The triadic teaching approach includes library-online searches that lead the students to design and conduct investigations, to carrying out mini-scientific symposia, and to preparing and conducting poster presentations open to the entire student body and faculty. The results of a 30-item Likert scale, administered to the students as a pretest and a posttest, indicated that there were significant increases in positive attitudes towards STS issues from the beginning to the end of the study. Individual interviews were also conducted with the students to determine the individual effects of each component of the triadic teaching approach on their attitudes towards STS issues. All aspects of the new approach provided significant contributions to the development of more positive attitudes among the students towards STS via interviews and on all sub-scales of a survey administered that include: (1) pupil interest in STS issues; (2) teacher interest in STS issues; (3) general perceptions regarding importance of STS issues.
Keywords: Science teacher education; Science-technology-society; Attitudes towards science-technology-society issues